Passiflora Incarnata Linn: A Review on Morphology, Phytochemistry and Pharmacological Aspects - Sharan Patel, Sita; Verma, Neelesh Kumar; Gauthaman, Karunakaran (Pharmacognosy Reviews)
This review gives an account of the current knowledge on the morphology, phytochemistry and pharmacological aspects of Passiflora incarnata. A wide range of chemical compounds has been isolated, mainly alkaloids, flavonoids, phenols and carbohydrates. P. incarnata has been described as passion flower and used extensively for treatment of several diseases like anxiety, insomnia, convulsion, sexual dysfunction, cough and cancer. Hence the present article includes the detailed exploration of morphology, phytochemistry and pharmacological aspects of P. incarnata is an attempt to provide a direction for further research.
Keywords: Passiflora incarnata; Aphrodisiac; Benzoflavone; Anti cancer; Cannabinoids